1999
DOI: 10.2337/diabetes.48.3.507
|View full text |Cite
|
Sign up to set email alerts
|

The homeodomain protein IDX-1 increases after an early burst of proliferation during pancreatic regeneration.

Abstract: Islet duodenal homeobox 1 (IDX-1/PF-1/STF-1/PDX-1), a homeodomain protein that transactivates the insulin promoter, has been shown by targeted gene ablation to be required for pancreatic development. After 90% pancreatectomy (Px), the adult pancreas regenerates in a process recapitulating embryonic development, starting with a burst of proliferation in the epithelium of the common pancreatic duct. In this model, IDX-1 mRNA was detected by semiquantitative reverse transcription-polymerase chain reaction in tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
234
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(259 citation statements)
references
References 12 publications
23
234
1
1
Order By: Relevance
“…As a result, pdx1 mutants lack functional pancreatic tissue (Jonsson et al, 1994;Offield et al, 1996), and it has been suggested that pdx1 regulates pancreatic stem cell function. Consistent with this hypothesis, pdx1 expression is markedly increased in proliferating ductular cells during pancreatic regeneration (Kritzik et al, 1999;Sharma et al, 1999).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…As a result, pdx1 mutants lack functional pancreatic tissue (Jonsson et al, 1994;Offield et al, 1996), and it has been suggested that pdx1 regulates pancreatic stem cell function. Consistent with this hypothesis, pdx1 expression is markedly increased in proliferating ductular cells during pancreatic regeneration (Kritzik et al, 1999;Sharma et al, 1999).…”
supporting
confidence: 61%
“…1Z), as in identically staged wild-type zebrafish (Fig. 1Y) and the regenerating pancreas of mammals (Sharma et al, 1999).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Activation of Pdx1 in duct cells of the pancreas has also been observed following partial pancreatectomy in mice [85] and in insulin resistant Zucker fatty (ZF) rats [83]. Importantly in this regard, Pdx1 expression is often observed in proliferating duct cells [77,94,95], and such cells have been suggested to serve as substrate for β cell neogenesis, particularly in cases of adaptive hyperplasia or pancreas regeneration [92,[96][97][98][99]. A recent study suggests that Pdx1, in complex with TALE transcription factors, negatively regulates the duct-specific keratin 19 gene in mature duct cells [100].…”
Section: Role Of Pdx1 In Adaptive β Cell Hyperplasia and β Cell Regenmentioning
confidence: 98%
“…Based upon these studies, several mechanisms have been postulated: (a) increased β cell apoptosis via and Bcl-2), with resulting loss of downregulation of anti-apoptotic genes (Bcl XL functional cell mass [56,67], (b) loss of activity of key Pdx1 target genes whose products are involved in glucose-stimulated insulin transcription and secretion (including Glut2, glucokinase, MafA, Nkx6.1, insulin) [57,63,[68][69][70][71][72][73][74][75][76], and (d) loss of new β cell formation/regeneration [64,77]; in this regard, studies suggest that the action of glucagon-like peptide 1 (GLP1) in enhancing β cell growth and formation in the adult may rely upon activation of Pdx1 in β cells and potential precursor cell types, such as those residing within ducts [74,[78][79][80][81][82].…”
Section: Role Of Pdx1 In the Adult Pancreasmentioning
confidence: 99%